Remifentanil combined with dexmedetomidine on the analgesic effect of breast cancer patients undergoing modified radical mastectomy and the influence of perioperative T lymphocyte subsets - Zhang, Yanjun; Jiang, Wei; Luo, Xi (Frontiers in Surgery, 2022)
Objective: To study the analgesic effect of breast cancer patients undergoing radical mastectomy and the influence of perioperative T lymphocyte subsets by remifentanil combined with dexmedetomidine. Methods: 80 breast patients were divided into two group based on the anesthesia protocol. Patients in control group was given remifentanil for anesthesia induction and maintenance, and patients in research group was given remifentanil and dexmedetomidine for anesthesia induction and maintenance. We compared the anesthesia time, operation time, surgical blood loss, postoperative wake-up time, extubation time, incidence of adverse reactions, VAS score and T lymphocyte subsets in peripheral blood in the two groups of patients. Results: The baseline data including age, height, weight and BMI, and surgical characteristics including anesthesia time, operation time and bleeding volume all have no significant difference between two groups (P>0.05). Compared to control group, the time of wake up and extubation in patients of research group were all significantly decreased (P<0.05), and significantly decreased MBP and HR after loading dose of dexmedetomidine in research group (P<0.05). The VAS scores of patients at 4, 8, 12, 16, 20 and 24 after surgery in the research group are all significantly lower than those in the control group (P<0.05). Before induction of anesthesia, there was no significant difference in the ratio of CD4+, CD8+ and CD4+/CD8+ T lymphocytes in peripheral blood between the two groups (P>0.05). At 1h during operation and 24h after operation, the ratio of CD4+ and CD4+/CD8+ cells in the research group was significantly higher than these of the control group (P<0.05), while the ratio of CD8+ cells was lower than that of the control group (P<0.05). Conclusion: For breast cancer patients undergoing radical mastectomy, the use of remifentanil combined with dexmedetomidine can enhance postoperative analgesia and reduce postoperative immunosuppression.